SYNTHESIS OF SAFRYL KETONE FROM SAFROLE - Hanoch J Sohilait; Hardjono Sastrohamidjojo; Sabirin Matsjeh; J Stuart Grossert (Universitas Gadjah Mada, 2004)
Synthesis of safryl ketone from safrole has been achieved through conversion of allyl group to secondary alcohol, followed by oxidation with PCC-Al2O3. The oxymecuration-demercuration reaction of safrole with HgSO4-NaBH4 yields safryl alcohol (66.38%) and the oxidation of safryl alcohol with PCC-Al2O3 yields safryl ketone (62.92%). The structure elucidation of these products was conducted using Fourier Transformed Infra Red Spectroscopy (FTIR), Proton-Nuclear Magnetic Resonance (1H-NMR) and Mass Spectroscopy (MS).